(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this paper we present a classification of sources and the strategies used by writers of theses and research papers in order to identify a research gap in Humanities. Based both on a qualitative study and a corpus analysis, we aim to determine the variation of such communicative act (identifying a research gap) in theses and research papers in the Humanities. The results show that identifying a research gap is carried out in both genres, though it is more frequent in the theses, possibly due to its evaluative nature. Thus, regardless the genre, it is easy to present an own research gap (without the reference to other sources). Finally, data show that specific strategies for identifying a research gap in the Humanities are not the same in both genres that are analyzed.